Incidências de acidente vascular encefálico (AVE) na população da região metropolitana de Belém - BARROS, Talita Raissa Barros (2023)
The stroke can be characterized in two ways, ischemic or hemorrhagic stroke. The ischemic is caused by regional deprivation of blood, can be transitory or permanent, and the hemorrhagic corresponds to blood extravasation inside the skull, caused by a rupture of the intracranial vessel, that culminate generating a brain tissue injury by anoxia. The stroke is one of the biggest causes of death in the world, as it relates to the fast development of clinical signs of focal or global disorders of brain function. The stroke rates have only been increasing over the years, especially in low-economy countries. Therefore, this study has as the objective to do the epidemiological survey of stroke numbers in the metropolitan population of Belém /PA, based on data provided by the department of information technology of the single health system (DATASUS).